Ability, motivation and opportunity (AMO)-enhancing HRM practices and corporate environmental citizenship: the mediation effect of organizational ethical climate - Tay, Lee Chin; Tan, Fee Yean; Hon, Wei Leow (Penerbit Universiti Kebangsaan Malaysia, 2023)
Ability, Motivation and Opportunity (AMO)-enhancing is essential for the effective implementation of corporate environmental citizenship. However, previous studies neglect the link between AMO-enhancing HRM practices and corporate environmental citizenship. This has motivated the paper studies the influence of AMO-enhancing HRM practices on corporate environmental citizenship via the mediating role of organizational ethical climate. This study employed a quantitative approach in the form of survey questionnaires. Survey questionnaires were collected from 200 construction companies and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results revealed that ability and opportunity-enhancing HRM practices were found to positively influence corporate environmental citizenship. Motivation-enhancing HRM practices were insignificant in this regard. Similarly, organizational ethical climate did not prove to mediate the relationship between AMO-enhancing HRM practices and corporate environmental citizenship. Therefore, construction companies should invest heavily in ability and opportunity-enhancing HRM practices to pursue corporate environmental citizenship. Instead, construction companies can abandon motivation-enhancing HRM practices and organizational ethical climate if they have limited funds to improve corporate environmental citizenship. Ultimately, policy makers should use these findings to create strategies as guidance for the construction industry to achieve corporate environmental citizenship.